Networking Secrets : The Psychology Behind Powerful Connections. - Walker, Andrew P.; ProQuest (firma) (La Vergne : eBookit.com, 2025)
This book explores the psychology behind effective networking, offering practical strategies to build meaningful and authentic connections. It delves into key psychological principles such as emotional intelligence, nonverbal communication, and active listening, emphasizing the importance of trust, credibility, and a growth mindset. The book provides actionable guidance for overcoming social anxiety, crafting impactful first impressions, and leveraging storytelling to foster deeper relationships. It also addresses networking challenges unique to introverts and extroverts, the role of timing in building connections, and the increasing significance of digital networking in today's world. Designed for professionals, entrepreneurs, and individuals seeking personal growth, the book aims to equip readers with the tools to navigate networking situations with confidence and authenticity.
Building a Cohesive Personal Brand for Networking -- Expanding Your Professional Network -- Strategies for Connecting with Industry Leaders -- Utilizing Networking Events Effectively -- Building a Supportive Network -- Creating a Circle of Influence -- Nurturing Long-Term Relationships -- Utilizing Reciprocity in Networking -- The Principle of Reciprocity in Building Networks -- Offering Value to Strengthen Connections -- Cross-Cultural Networking -- Understanding Cultural Differences in Networking -- Strategies for Navigating Diverse Networking Environments -- Ethical Networking Practices -- Maintaining Integrity in Networking -- Avoiding Common Networking Pitfalls -- Networking for Career Advancement -- Leveraging Networks for Job Opportunities -- Building a Professional Support System -- Networking in Social Settings -- Utilizing Social Gatherings for Networking Purposes -- Adapting Strategies to Informal Environments -- The Impact of Follow-Ups -- The Importance of Timely Follow-Ups -- Techniques for Effective Follow-Through -- Assessing and Refining Your Network -- Evaluating the Strength of Your Connections -- Strategies to Reinforce and Refresh Your Network -- Sustaining Long-Lasting Relationships -- Techniques for Keeping Connections Alive -- Balancing Quantity and Quality in Networking -- Networking for Personal Growth -- Using Networks to Enhance Personal Development -- Aligning Networking Goals with Personal Aspirations -- Conclusion -- Appendix.
Description based on publisher supplied metadata and other sources.
Part of the metadata in this record was created by AI, based on the text of the resource.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2025. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Interpersonal communication; Emotional intelligence; elektronické knihy; electronic books